Pseudo-static low cycle test on the mechanical behavior of PHC pipe piles with consideration of soil-pile interaction. (15th September 2018) - Huang, Fu-yun; Wu, Sui-wen; Luo, Xiao-ye; Chen, Bao-chun; Lin, Youwei
Abstract: Pre-stressed high-strength concrete (PHC) pipe piles have been widely used in the pile foundations of buildings and bridges which are usually designed elastic based on the capacity design principle. However, when the PHC pipe pile comes to the foundations of Integral Abutment Jointless Bridges (IAJBs), limited ductility might apply in order to accommodate the relatively large deformation demand under the effect of temperature fluctuations or earthquake. The conventional design methods for PHC pipe piles remain in doubt. This paper focuses on low cycle pseudo-static tests on 4 PHC pipe-pile models with various pre-stress levels to gain insight into their mechanical behaviors with consideration of soil-pile interaction. Medium sand was employed in the tests. The details of the experiments are introduced, including design of the models, instrumentation and loading scheme. The testing results indicate that the damages of the PHC pipe piles are mainly concentrated at 4D to 8D of embedded depths. Moreover, the pre-stress level and reinforcement ratio have a significant influence on the failure mode of PHC pipe piles, especially on the distribution of internal force and moment along piles. It is found that the interaction effect of pile-soil strengthens with the pre-stress level which is beneficial to the seismic performance. Furthermore, the backbone of the PHC pipe piles model has four stages: elastic, elastic-plastic, plastic hardening, and failure. It is concluded that PHC pipe piles perform favorably plastic and ductile behavior, and their failure modes are flexural (bending) not brittle (shear). Finally, the PHC pipe pile has an appreciable energy dissipation and deformation capacity, and hence can be used for pile foundations in IAJBs.